Growing Craze in the Use of English in Nepali Public Domains - Dewan, Shankar; Saud, Mohan Singh (The Outlook: Journal of English Studies, 2022)
English in Nepal is taken as a foreign language but ground reality shows that it is one of the primary and dominant languages, which is extensively used in various spheres such as academic institutions, technology, business, tourism, social gatherings, and daily lives. This study attempts to analyze the growing craze in the use of English in Nepali public domains. We collected qualitative data from both primary and secondary sources. We purposively selected names of academic institutions, public vehicles, persons, places and things, Nepali movies, two billboards, one text from the social media, two teachers as well as our own experiences. The result reveals that there has been a growing craze in the use of English in Nepali discourses and public domains, along with code-mixing in speech and writing. Extensive use of English in naming, academic institutions, media, and everyday discourses justify that English is growing as a primary and dominant language in Nepal. Therefore, this study suggests that it is necessary to reassess the status and functions of English in Nepal and give it an official status.